2016
DOI: 10.1186/s12914-016-0082-2
|View full text |Cite
|
Sign up to set email alerts
|

Parenthood in transition – Somali-born parents’ experiences of and needs for parenting support programmes

Abstract: BackgroundPre- and post-migration trauma due to forced migration may impact negatively on parents’ ability to care for their children. Little qualitative work has examined Somali-born refugees’ experiences. The aim of this study is to explore Somali-born refugees’ experiences and challenges of being parents in Sweden, and the support they need in their parenting.MethodsA qualitative descriptive study was undertaken. Data were collected from four focus group discussions (FGDs) among 23 Somali-born mothers and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
146
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(149 citation statements)
references
References 28 publications
3
146
0
Order By: Relevance
“…While several studies have examined the parent perspective on family relationships and the process of cultural adaptation [45, 47, 48], our study highlights the importance of also including the perspective of young people, as family dynamics are complicated and more nuanced. Important differences emerged in the views of adults and youth.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…While several studies have examined the parent perspective on family relationships and the process of cultural adaptation [45, 47, 48], our study highlights the importance of also including the perspective of young people, as family dynamics are complicated and more nuanced. Important differences emerged in the views of adults and youth.…”
Section: Discussionmentioning
confidence: 95%
“…Unlike in Somalia, where children could move around freely, many parents voiced concern over their children’s safety and felt children required close monitoring and supervision [45, 46]. Parents also expressed concerns over changes in parenting power, lack of disciplinary authority, and children not respecting parents [38, 45, 47, 48]. Many of these challenges were attributed to the influence of Western culture on children [38, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Moving to a new country and adapting to a new way of life can present obstacles for immigrant parents and their children and create tension and stress within families . Studies have shown that it is often easier for children than parents to acculturate to a new country and that they sometimes serve as the parents’ primary source of information . The changes in family functions, and the new roles that emerge because of immigration, may have a negative impact on parent–child relationships .…”
Section: Introductionmentioning
confidence: 99%
“…Such a parenting approach, which insists on unquestioning obedience, might lead to conflicts between parents and children in the new country. In these cases, parents may need extra support to bring up their children . Another notable strain on immigrant parents is inadequate information about the parenting systems and social expectations for parents in the new country.…”
Section: Introductionmentioning
confidence: 99%
“…Reported models are usually multi‐family groups influenced by systemic and narrative theories. These combine psychoeducation with specific themes like families in transition, impact of past and current trauma on the family unit, role changes and coping strategies by family members (Bjorn, Boden, Sydsjo, & Gustaffson, ; Osman, Klingberg‐Alvin, Flacking, & Schon, ; Slobodin & de Jong, ). Parenting interventions such as the Parent Management Training (Bjorknes & Manger, ) and Parenting in a New Culture (Renzaho & Vignjevic, ) have been culturally adapted with similar positive outcomes as in the general population, albeit with a concurrent focus in reducing harsh discipline and instilling positive skills.…”
Section: Introductionmentioning
confidence: 99%